HUMAN VISCERAL LEISHMANIASIS: AN INTERDISCIPLINARY HEALTH PERSPECTIVE ON ASPECTS OF TERRITORY AND CULTURE - da Silva, Marivaldo Cavalcante; Queiroz, Julia Eduarda Campos (Editora Impacto Científico, 2025)
Considered a reemerging disease, Visceral Leishmaniasis – VL, both canine and human, is expanding in Brazil, being endemic in 12 countries in the Americas. It is considering the social, cultural, as well as environmental dimensions, discussing interdisciplinary perspectives, starting from a discussion and recognition of the concepts of health, territory and culture, that this article seeks to contribute to the reflection on these concepts, their importance in the structuring and implementation of the actions offered by the SUS in the study and fight against Human Visceral Leishmaniasis – HVL. For the construction of this work, a search was carried out in publications of scientific articles, theses and books. One of the possibilities for studying and combating HVL may be to strengthen the community through intersectoral actions, to overcome conflicts between health agents and the community with the recognition of the territory, health practices and daily life, among many other possible possibilities. DOI: 10.56238/edimpacto2025.060-004